Leisure and Physical Education in Schools: Teaching Experience in a Public School of Mato Grosso (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2012)
This study describes a teaching experience with middle school students in a public school in the interior of Mato Grosso, in the discipline of physical education. This experience was based on the perspective of education for leisure. In physical education classes at school predominates the teaching of the sport. This element of the culture is strongly influenced by professional competition sports and by mass media. The sports are often worked in physical education classes with technical emphasis and repetition, without due criticism, offering little contribution to the formation of students. In this sense, physical education classes that enable students to access knowledge of body culture, from the perspective of education for leisure, can be a contribution, so that students can benefit of quality leisure times, being creative and critical. As a result, it is noted that education for leisure is a theoretical and practical possibility to be explored in school.